Effect of commercially available probiotics on quality parameters of plain yogurts - CUEVAS, Vanessa Martínez; SARQUIS, Lizza; CONTRERA, Ana María; RAMÍREZ, Judith; ALI, Sher; OLIVEIRA, Carlos Augusto Fernandes de (Food Science and Technology, 2024)
This study evaluated the effect of two commercially available probiotics (Bifidobacterium animalis BB-12®, Chr. Hansen, and Lacticaseibacillus rhamnosus + Lacticaseibacillus paracasei culture FreshQ®9, Chr. Hansen) on quality parameters of plain yogurts and the development of Aspergillus sp. and Escherichia coli inoculated in the products. Sensory evaluations were performed on the second day after the manufacture of yogurts, while microbiological analysis and pH measurements were carried out at 5-day intervals during 30 days of storage at 4°C. Yogurt containing FreshQ®9 had lower pH values and reduced fermentation time than control or BB-12® yogurts, also presenting higher sensory grades. Aspergillus sp. and E. coli counts decreased in all types of yogurts, although the probiotic cultures did not affect these microbial adulterants. Data indicate that L. rhamnosus in combination with L. paracasei improved the overall quality of yogurt. Further studies are needed to explore the potential bioprotective effect of the evaluated probiotics against other spoilage microorganisms in yogurt.